Discourse in Translation - Faiq, Said (Taylor & Francis, 2019)
This book explores the discourse in and of translation within and across cultures and languages. From the macro aspects of translation as an inter- cultural project to actual analysis of textual ingredients that contribute to translation and interpreting as discourse, the ten chapters represent different explorations of 'global' theories of discourse and translation. Offering interrogations of theories and practices within different sociocultural environments and traditions (Eastern and Western), Discourse in Translation considers a plethora of domains, including historiography, ethics, technical and legal discourse, subtitling, and the politics of media translation as representation. This is key reading for all those working on translation and discourse within translation studies and linguistics.